SOCIOLINGUISTIC ANALYSIS OF COMMUNICATION UNITS IN TAHIR MALIK'S NOVEL "SHAYTANAT" - Malika, Dadebaeva (Journal of Higher Education and Academic Advancement, 2024)
Selling tours is beneficial for both parties - tour operators and clients, providing the opportunity to gain access to a variety of travel offers and save on travel